Use of RIP to inactivate genes in Neurospora crassa. - E. Selker; E. Cambareri; P. Garrett; B. Jensen; K. Haack; E. Foss; C. Turpen; M. Singer; J. Kinsey (Fungal Genetics Reports, 1989)
About two years ago we suggested that a novel genetic mechanism, operating in the period between fertilization and nuclear fusion in Neurospora, scans the genome for sequence dupliations and alters them (Selker E. et al. 1987 Cell 51:741-752).